MUATAN NILAI KARAKTER DALAM CERITA RAKYAT KIAI PACET DAN RARA KEMBANG SORE - Rahmawati Mulyaningtyas; Dian Etikasari (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2022)
The Content of Character Values in the Folklore of Kiai Pacet and Rara Kembang Sore. The purposes of this research are a) to describe the character values in the folklore of Kiai Pacet and Rara Kembang Sore and b) to describe the function of character values in the folklore. This research uses a qualitative approach with content analysis research methods. The source of data in this research is the text of the Tulungagung folklore (Kiai Pacet and Rara Kembang Sore) contained in the East Java Folklore anthology published by the East Java Language Center in 2011. The data for this research are narratives and dialogues from two folklore texts. The results show that the values contained in the folklore of Kiai Pacet and Rara Kembang Sore are religiousness, honesty, tolerance, creativity, curiousity, appreciation of achievement, love of peace, responsibility, and social care. The function of character values in the two folklores are the shaping and developing the potentials, improvements and strengthening, and filtering  functions.